Updates On Laboratory Tests For Diagnosis Of Glucose-6-phosphate Dehydrogenase Deficiency In Malaysia - Alina Md Fauzi; Raja Zahratul Azma Raja Sabudin; Darnina Abdul Jalil; Azlin Ithnin; Hafiza Alauddin; Cheah Fook-Choe; Najiah-Ajlaa Ayub; Moh Yusuf Malisa; Jalil Norunaluwar; Othman Ainoon (Informa Healthcare, 2024)
Indexed by ERA